Comparative Transcriptomic Analysis of Rhinovirus and Influenza Virus Infection - Dissanayake, Thrimendra Kaushika; Schäuble, Sascha; Mirhakkak, Mohammad Hassan; Wu, Wai-Lan; Ng, Anthony Chin-Ki; Yip, Cyril C. Y.; López, Albert García; Wolf, Thomas; Yeung, Man-Lung; Chan, Kwok-Hung; Yuen, Kwok-Yung; Panagiotou, Gianni; et al. (Frontiers in Microbiology, 2020)
Rhinovirus and influenza virus are the most frequently detected respiratory viruses among adult patients with community acquired pneumonia. Previous clinical studies have identified major differences in the clinical presentations and inflammatory or immune response during these infections. A systematic transcriptomic analysis directly comparing influenza and rhinovirus is lacking. Here, we sought to compare the transcriptomic response to these viral infections. Human airway epithelial Calu-3 cells were infected with contemporary clinical isolates of rhinovirus, influenza A virus (IAV), or influenza B virus (IBV). Host gene expression was determined using RNA-seq. Differentially expressed genes (DEGs) with respect to mockinfected cells were identified using the overlapping gene-set of four different statistical models.Transcriptomic analysis showed that rhinovirus-infected cells have a more blunted host response with fewer DEGs than IAV or IBV-infected cells. IFNL1 and CXCL10 were among the most upregulated DEGs during rhinovirus, IAV and IBV infection. Other DEGs that were highly expressed for all 3 viruses were mainly genes related to type I or type III interferons (RSAD2, IDO1) and chemokines (CXCL11). Notably, ICAM5, a known receptor for enterovirus D68, was highly expressed during rhinovirus infection only. Gene Set Enrichment Analysis (GSEA) confirmed that pathways associated with interferon response, innate immunity, or regulation of inflammatory response, were most perturbed for all 3 viruses. Network analysis showed that steroid-related pathways were enriched. Taken together, our data using contemporary strains suggests that genes related to interferon and chemokine predominated the host response associated with rhinovirus, IAV and IBV infection. Several highly expressed genes, especially ICAM5 which is preferentially-induced during rhinovirus infection, deserve further investigation.